(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The Boldha garden, Dhaka, is rich in Bryophyte flora because of its special micro?environment. The present paper on Hepaticopsida and Bryopsida includes an account of 32 species under 12 genera, 10 families and 8 orders. A short taxonomic description of each species with locations, date of collection, name of collectors and alphabetic arrangement of taxa are provided. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20094 Dhaka Univ. J. Biol. Sci. 23(2): 147-156, 2014